The Cultural Practice of Immigrant Filmmaking Minor Immigrant Cinemas in Sweden 1950-1990 - Andersson, Lars Gustaf; Sundholm, John (Intellect, 2019)
Based on a research project funded by the Swedish Research Council, this book analyses 40 years of post-war independent immigrant filmmaking in Sweden. John Sundholm and Lars Gustaf Andersson consider the creativity that lies in the state of exile, offering analyses of over 50 rarely seen immigrant films that would otherwise remain invisible and unarchived. They shed light on the complex web of personal, economic and cultural circumstances around migrant filmmaking, and discuss associations that became important sites of self-organization for exiled filmmakers: The Independent Film Group, The Stockholm Film Workshop, Cineco, Kaleidoscope and Tensta Film Association.
Description based on print version record.
KU Open Services
Keywords: Social Science / Emigration & Immigration; Social sciences; Electronic books